A Genomic Snapshot of the SARS-CoV-2 Pandemic in the Balearic Islands - López-Causapé, Carla; Fraile-Ribot, Pablo A.; Jiménez-Serrano, Santiago; Cabot, Gabriel; del Barrio-Tofiño, Ester; Prado, M. Carmen; Linares, Juana María; López, Aranzazu; Hurtado, Adoración; Riera, Elena; Serra, Antoni; Roselló, Eva; et al. (Frontiers in Microbiology, 2022)
Objective: To analyze the SARS-CoV-2 genomic epidemiology in the Balearic Islands, a unique setting in which the course of the pandemic has been influenced by a complex interplay between insularity, severe social restrictions and tourism travels. Methods: Since the onset of the pandemic, more than 2,700 SARS-CoV-2 positive respiratory samples have been randomly selected and sequenced in the Balearic Islands. Genetic diversity of circulating variants was assessed by lineage assignment of consensus whole genome sequences with PANGOLIN and investigation of additional spike mutations. Results: Consensus sequences were assigned to 46 different PANGO lineages and, 75% of genomes were classified within a VOC, VUI or VUM variant according to the WHO definitions. Highest genetic diversity was documented in the island of Majorca (42 different lineages detected). Globally, lineages B.1.1.7 and B.1.617.2/AY.X were identified as the 2 major lineages circulating in the Balearic Islands during the pandemic, distantly followed by lineages B.1.177/B.1.177.X. However, in Ibiza/Formentera lineage distribution was slightly different and lineage B.1.221 was the third most prevalent lineage. Temporal distribution analysis showed that B.1 and B.1.5 lineages dominated the first epidemic wave, lineage B.1.177 dominated the second and third, and lineage B.1.617.2 the fourth. Of note, lineage B.1.1.7 became the most prevalent circulating lineage during first half of 2021; however, it was not associated with an increased in COVID-19 cases likely due to severe social restrictions and limited travels. Additional spike mutations were rarely documented with the exception of mutation S:Q613H which has been detected in several genomes (n=25) since July 2021. Conclusion: Virus evolution, mainly driven by the acquisition and selection of spike substitutions conferring biological advantages, and social restrictions are key factors for explaining the epidemic patterns registered in the Balearic Islands.